Extraction of Aluminium (Al) Metal from Coal Fly Ash of PLTU-Paiton with NaOH Solvent - Puspa, Aranca Nindya; Haryati, Tanti; Andarini, Novita (Indonesian Chimica Letters, 2023)
Fly ash, a solid waste product from the coal combustion process at the Paiton PLTU, contains 14.52-23.78% alumina (Al2O3). This can be extracted using NaOH for further utilization. The Al(OH)3 precipitate was obtained using a 4 M HCl solution with pH variations of 6 and 6.5. Meanwhile, Al metal was obtained using a reduction temperature variation of 600-700°C with an interval of 50°C using Mg metal reductant for 2.5 hours. The aluminum metal obtained was subjected to qualitative analysis by UV-Vis spectrophotometer and quantitative analysis by XRF and AAS. The Al(OH)3 precipitate obtained at a pH of 6.001 weighed 1.581 grams, with a yield of 61.83%, while at a pH of 6.500 it weighed 1.688 grams, with a yield of 66.02%. Applying a specific reagent for Al metal, alizarin, to qualitative analysis resulted in a maximum wavelength of 495 nm. A quantitative analysis was conducted utilizing the atomic absorption spectrophotometer (AAS) at a wavelength of 309.3 nm. The alumina content in fly ash was determined to be 14.52%, with an Al metal yield of 8.67% at a pH of 6 and 9.01% at a pH of 6.5, at an optimal reduction temperature of 650°C.